Electron irradiation of Co, Ni, and P-doped BaFe2As2-type iron-based superconductors - van der Beek, C.J.; Demirdis,S.; Colson, D.; Rullier-Albenque, F.; Fasano, Y.; Shibauchi, T.; Matsuda, Y.; Kasahara, S.; Gierlowski, P.; Konczykowski, M.; Fasano, Yanina (IOP Publishing, 2013)
Fil: Fasano, Y. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina